The oncolytic virus Delta-24-RGD elicits an antitumor effect in pediatric glioma and DIPG mouse models - Naiara Martínez-Vélez; Marc Garcia-Moure; Miguel Marigil; Marisol González-Huarriz; Montse Puigdelloses; Jaime Gallego Pérez-Larraya; Marta Zalacaín; Lucía Marrodán; Maider Varela-Guruceaga; Virginia Laspidea; Jose Javier Aristu; Luis Isaac Ramos; et al. (Nature Communications, 2019)
The oncolytic virus Delta-24-RGD is in clinical trial for adult glioma. Here, the authors show that this virus elicits an immune response in mouse models of pediatric high-grade glioma and diffuse pontine intrinsic glioma, resulting in improved survival.